Inovasi Konten Digital sebagai Pendorong Pertumbuhan Bisnis Generasi Z - Muhammad Alfian Solo; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACT The digital era has created new opportunities for Generation Z to develop businesses through the use of innovative creative content. This article focuses on how digital content innovation serves as a key driver of business growth among Gen Z, particularly amid the increasingly competitive landscape of digital platforms. This study employs a literature review method with a conceptual analysis approach, synthesizing various academic sources, industry reports, and previous research related to content innovation, Gen Z digital behavior, and modern business growth strategies. Data were collected through systematic searches across multiple scholarly databases and analyzed using content analysis techniques to identify patterns, theoretical trends, and interconcept relationships. The findings indicate that digital content innovation not only enhances visibility and engagement but also strengthens brand image, expands market reach, and builds emotional connections with audiences. Generation Z has demonstrated the ability to leverage creativity, trend literacy, and platform algorithm comprehension to produce relevant and valuable content. Additionally, digital collaboration and active participation in online communities foster consumer trust and promote sustainable business growth. This study underscores that digital content innovation is a crucial pillar in navigating the dynamics of business in the Society 5.0 era and stands as a primary strategy for Generation Z to achieve stronger competitiveness.